2001
DOI: 10.1021/ja0035452
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Structure and Properties of Transition Metal−Benzene Complexes

Abstract: A comprehensive theoretical study of the geometries, energetics, and electronic structure of neutral and charged 3d transition metal atoms (M) interacting with benzene molecules (Bz) is carried out using density functional theory and generalized gradient approximation for the exchange-correlation potential. The variation of the metal-benzene distances, dissociation energies, ionization potentials, electron affinities, and spin multiplicities across the 3d series in MBz complexes differs qualitatively from thos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

31
205
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(239 citation statements)
references
References 36 publications
31
205
3
Order By: Relevance
“…A subsequent density functional study confirmed the FM coupling in multidecker sandwich V n (Bz) n+1 clusters [8]. Motivated by the above experimental and theoretical studies, we propose that the 1D organometallic sandwich polymers [V(Bz)] ∞ are the possible candidates for spintronic devices for spinpolarized transport since the polymers with an inherently uniform size are supposed to be also FM.Metal-ligand molecules have been the subject of many studies in the past decade [9,10,11,12,13,14,15,16]. Especially, TM-Bz complexes (M n (Bz) m ) are the prototypical organometallic complexes for studying the d−π bonding interactions.…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…A subsequent density functional study confirmed the FM coupling in multidecker sandwich V n (Bz) n+1 clusters [8]. Motivated by the above experimental and theoretical studies, we propose that the 1D organometallic sandwich polymers [V(Bz)] ∞ are the possible candidates for spintronic devices for spinpolarized transport since the polymers with an inherently uniform size are supposed to be also FM.Metal-ligand molecules have been the subject of many studies in the past decade [9,10,11,12,13,14,15,16]. Especially, TM-Bz complexes (M n (Bz) m ) are the prototypical organometallic complexes for studying the d−π bonding interactions.…”
mentioning
confidence: 80%
“…Metal-ligand molecules have been the subject of many studies in the past decade [9,10,11,12,13,14,15,16]. Especially, TM-Bz complexes (M n (Bz) m ) are the prototypical organometallic complexes for studying the d−π bonding interactions.…”
mentioning
confidence: 99%
“…The structure of the C 6 H 6 -Ti complex has been theoretically [20][21][22][23][24][25][26][27] and experimentally [28] studied on the basis of DFT calculations and laser evaporation methods. Experimental evidence indicates the ground state to be a triplet in a planar C 6v configuration.…”
Section: Orbital Interactions and Bonding In Cmentioning
confidence: 99%
“…The isolobal relationship between arenes and nano carbon materials suggests that the coordination of metals to their surface should be facile [1]. In particular, η 6 -coordination of the Group 6 metals (Cr, Mo, and W) should be possible.…”
Section: Introductionmentioning
confidence: 99%